A training course on basic gynecological clinical skills and its effect on medical student’s performance in Guilan University of Medical Sciences - Hajar Sharemi; fariba Asgari (مجله ایرانی آموزش در علوم پزشکی, 2011)
Introduction: Pursuing the purpose of promoting students’ potentials for learning practical skills, medical universities have tried to create a suitable environment in clinical skills centers for the practice of medicine in a simulated environment to prevent possible mistakes in real-life situations. This study aims to determine the effect of basic gynecological clinical skills on students’ performance in Guilan University of Medical Sciences. Methods: This quasi-experimental study with a single before-and-after-training group conducted in April 2009 in the Clinical Skills Center of Guilan University of Medical Sciences. Through census sampling 25 clerckship students taking the basic gynecological clinical skills course were studied. Data collection was done through 8 researcher-built checklists. Their validity and reliability were confirmed .Descriptive (mean and standard deviation) and inferential (paired t-test) statistics were applied for data analysis using SPSS. Results: There was a significant difference between the students’ performance on basic gynecological clinical skills before and after training the mean of the students’ total scores on all eight skills showed a significant increase after the training course. The highest mean scores before the training belonged to pop smear sampling skill(7.12w±2.42) and IUD insertion skill (5.8±2.41),while the lowest belonged to the management of third stage of labor skill(1.33±0.57) and bimanual examination skill (1.8±0.18). Skills which showed the highest mean scores after the training were IUD Insertion skill (13.52 ± 1.29) and Pap smear sampling skill(12± 1.08). Conclusion:Before the skills training, the students’ mean scores on most procedures were not satisfactory, but after the training course, they increased significantly. Therefore, it is suggested that clinical skills centers and objective assessment methods be used both to meet students’ needs and preserve patients’ rights.